(3JKbja GddSGf hJdbjM GdLfGfs - (3GHf ecj GdUbdj, YeQ Hf Nda,s (3J(B. 501 (3g`(B.s; (3eWQ, YHO GdYRjRs ((3GdbGgQI (B:s (3GdeLdS GdCYdi ddTDhf GdESdGejI,s, 1995)
(3HGH GdJUMja(B.s
Keywords: (3GdCNWGA GddZhjIs; (3GddZI GdYQHjIs -- (3bhGYO GdEedGA hGdgLGAs